Vinirmāṇaṃ - Nārāyaṇareḍḍi, Suṅkireḍḍi (Kavile, Telaṅgāṇa Rēserc & Repharāl Seṇṭar, 2021)
Critical essays on Telangana identity in Telugu literature
Enthält Literaturangaben
Keywords: Telangana; Telugu-Sprache; Literatur; Politische Identität